Vein structure in relation to phloem loading in selected Ranunculaceae, Apocynaceae and Asclepiadaceae of the Eastern Cape - Buswell, Alison Mary (Rhodes University, Faculty of Science, Botany Department, 2001)
The relationship between leaf architecture, vein anatomy and phloem ultrastructure, and that of possible routes from mesophyll cells to phloem and potential phloem loading method was investigated using species adapted to the southern African climate. The research was based on the hypothesis of Gamaiei and Van Bel, using nothern hemisphere species only (Gamalei 1985a, b, 1989, 1991, VanBeletal. 1988, Van Bel 1992, 1994, 1996, Van Bel & Gamalei 1991, 1992, Gamalei et al. 1992, 1994, 1996, Van Bel 1992a-c, 1993a, b, 1996). The thesis commenced with a survey ofleafarchitecture of the Ranunculaceae, Apocynaceae and Asclepiadaceae. Anatomical and ultrastructural studies followed. Leaf architecture was described according to Hickey (1973). Within the Ranuncuiaceae, leaf architecture was found to be marginally actinodromous. Venation pattern consisted of a widely spaced reticulum of delicate veins, especially in Ranunculus. Leaf architecture of the Apocynaceae was described as pinnate, camptodromous and brochidodromous. The Asclepiadaceae showed less uniformity in terms of leaf architecture, being pinnate and camptodromous, with mostly brochidodromous and, unexpectedly, eucamptodromous patterns of secondary venation. A predominantly common leaf architecture supported the move to amalgamate the two families. As the less advanced eucamptodromous arrangement could represent a more primitive branch of this huge family, the phylogenetic classification of the new amalgamated family is eagerly awaited for discussion. Allocation of vein order allowed comparisons between species and families to be drawn. Reticulum density and vein order anatomy was used to indicate potential routes from mesophyll to phloem. A definite contrast was obvious between the loose arrangement of mesophyll and veins in the mesic Ranunculus, and the close mesophyll and dense venation of the xeric apocynate and asclepiad species, and was related to habitat. Ultrastructural characteristics of companion cells, together with plasmodesmatal abundance, were considered especially important for the determination of minor vein configuration. Descriptions of plasmodesmatal distribution did not consider functional status. In this thesis, vein structure and ultrastructure were considered in relation to phloem loading, not as a demonstration thereof. All three families were designated minor vein configuration type 2a. Two interesting examples that did not adhere to the familial norm, viz. few plasmodesmata and normal companion cells, occurred in the Asclepiadaceae. Secamone alpinii had abundant aggregated plasmodesmata, forming a potential symplasmic continuum from mesophyll to companion cells. The question of plasmodesmatal functionality remained open. Ceropegia carnosa showed folding of the companion cell membrane, but no accompanying wall ingrowths. The folds were suggested to increase surface area for apoplasmic phloem loading in the noted absence of plasmodesmata. Loading routes and methods suggested were based on anatomical and ultrastructural evidence only. Whilst these results were supported by published data for other species of these families, the prediction of the Gamalei and Van Bel hypothesis did not hold true. The relatively primitive Ranunculaceae were expected to have the least advanced type 1 minor vein configuration, with abundance plasmodesmata providing a symplasmic phloem loading pathway. The relatively advanced Apocynaceae and Asc1epiadaceae were predicted to have the most progressive minor vein configuration, type 2b, with specialised transfer cells to maximise apoplasrnic uptake. As families with type 2a minor vein configurations, the Ranunculaceae were more advanced than expected and the Apocynaceae and Asc1epiadaceae less so.
Keywords: Ranunculaceae; Apocynaceae; Asclepiadaceae; Phloem; Plants -- South Africa -- Eastern Cape